Biomolecule-derived quantum dots for sustainable optoelectronics. Issue 3 (21st January 2019) - Bhandari, Satyapriya; Mondal, Dibyendu; Nataraj, S. K.; Balakrishna, R. Geetha
Abstract : The recent advances in sustainable optoelectronics applications of quantum dots derived from different biomolecules are documented in this review. Abstract : The diverse chemical functionalities and wide availability of biomolecules make them essential and cost-effective resources for the fabrication of zero-dimensional quantum dots (QDs, also known as bio-dots) with extraordinary properties, such as high photoluminescence quantum yield, tunable emission, photo and chemical stability, excellent aqueous solubility, scalability, and biocompatibility. The additional advantages of scalability, tunable optical features and presence of heteroatoms make them suitable alternatives to conventional metal-based semiconductor QDs in the field of bioimaging, biosensing, drug delivery, solar cells, photocatalysis, and light-emitting devices. Furthermore, a recent focus of the scientific community has been on QD-based sustainable optoelectronics due to the primary concern of partially mitigating the current energy demand without affecting the environment. Hence, it is noteworthy to focus on the sustainable optoelectronic applications of biomolecule-derived QDs, which have tunable optical features, biocompatibility and the scope of scalability. This review addresses the recent advances in the synthesis, properties, and optoelectronic applications of biomolecule-derived QDs (especially, carbon- and graphene-based QDs (C-QDs and G-QDs, respectively)) and discloses their merits and disadvantages, challenges and future prospects in the field of sustainable optoelectronics. In brief, the current review focuses on two major issues: (i) the advantages of two families of carbon nanomaterials ( i.e. C-QDs and G-QDs) derived from biomolecules of various categories, for instance (a) plant extracts including fruits, flowers, leaves, seeds, peels, and vegetables; (b) simple sugars and polysaccharides; (c) different amino acids and proteins; (d) nucleic acids, bacteria and fungi; and (e) biomasses and their waste and (ii) their applications as light-emitting diodes (LEDs), display systems, solar cells, photocatalysts and photo detectors. This review will not only bring a new paradigm towards the construction of advanced, sustainable and environment-friendly optoelectronic devices using natural resources and waste, but also provides critical insights to inspire researchers ranging from material chemists and chemical engineers to biotechnologists to search for exciting developments of this field and consequently make an advance step towards future bio-optoelectronics.